Clinical and morphological comparison of respiratory failure in patients with COVID-19 who died under different options of respiratory support - Skoryk, Vita; Korsunov, Volodymyr; Bocharova, Tetiana; Nartov, Pavel; Valentina, Maslova (ScienceRise: Medical Science, 2021)
The aim. Based on the study of the effect of invasive mechanical ventilation and NIV in the CPAP mode on the pathomorphosis of lung damage in patients with HRF caused by SARS-nCoV-2 and deaths in intensive care unit (ICU), determine the safest method of respiratory support. Materials and methods. The study included morphological material from 20 patients with HRF caused by SARS-nCoV-2 (COVID-19) who died in ICU. Group 1 included patients who received non-invasive lung ventilation in CPAP mode through a face mask (n=10), group 2 - patients who underwent invasive ventilation (n=10). The prepared sections, 5 μm thick, were stained according to the Van Gizon method. Photomicrographs were taken using Zeiss ZENliteimaging. Data are presented as M [25-75] and P±Sp. Statistical analysis of the results was performed using the program “Statistica 10”. Significance of differences in indicators was assessed using the nonparametric Wilcoxon test, the parametric Student's test. The results were considered reliable at values of p<0.05. Results The morphological structure of the lungs of patients of group 1 corresponded to the exudative phase of DAD with severe edematous-hemorrhagic syndrome, signs of interstitial pneumonia with desquamation of alveolocytes and the formation of hyaline membranes. In patients of group 2 in the lung tissue there was a picture of the proliferative phase of DAD with signs of interstitial pneumonia, and the development of focal fibrosing alveolitis. Thus, invasive mechanical ventilation, can accelerate the development of irreversible processes in the lungs in the form of fibrosing alveolitis and promote the formation of ventilator-associated pneumonia Conclusions. CPAP NIV is a promising method of respiratory support in patients with ARDS caused by SARS-nCoV-2 virus (COVID-19), which needs further study